Licence verbale et mouvements contestataires chez les Haal pulareeɓe du Fuuta Tooro Almudaagal ngay et Cooloyaagal - Ibrahima Abou Sali (Revue des Mondes Musulmans et de la Méditerranée)
Insult among the Fulbe can play an important role, although it is not well accepted by the surrounding society. This is exemplified by two protest movements, the Almudaagal ngay and the Cooloyaagal that succeeded to impose themselves among the Haal pulareebe from Mauritiania/Senegal. But the two movements did not come out from the same social groups. One was coming from a high status group, who edicted the social and moral values. The other was coming from a low level group. The distinction between the two groups was reflected in their respective use of insult. The stricto sensu insult, the yƴattoore, characterized by hard sexual connotations, was used only among the members of the low social group. Among the Almuɓɓe ngay, members of the high level group, punctual contestation was considered as a kind of therapeutically action aiming at the students' integration within the establishment. Whereas among the Coolooji, originating from the lowl level groups, and therefore excluded from the dominant ideology, contestation was mainly a social critic.